Syphilitic hepatitis: a rare complication of secondary syphilis. A case report - Margarida Caldeira; Ana L. João; Mafalda Pestana; I. Canha; G. Simões; C. Fernandes (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Syphilis is a sexually transmitted disease caused by Treponema pallidum, progressing through active and latent stages if left untreated. Hepatic involvement can occur in secondary syphilis, but this is an uncommon complication, with few published case reports. A 34-year-old man without significant medical history was admitted to the gastroenterology department with a 2-week history of unexplained jaundice and acute cholestatic hepatitis. He also presented with erythematous papules and plaques in the genital area, suggestive of secondary syphilis. T. pallidum hemaglutination assay and venereal disease research laboratory test were both positive, the latter with a 1:16 titer. The diagnosis of secondary syphilis with hepatic involvement was considered. The improvement of cutaneous and laboratory findings after intramuscular benzathine penicillin injection supported this hypothesis. Symptomatic cholestatic hepatitis is a rare feature of the systemic spectrum of secondary syphilis. The clinical and laboratorial response after penicillin treatment is a strong clue for this diagnosis.